2021
DOI: 10.2147/ijwh.s314780
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Premature Rupture of Membranes Among Pregnant Women Admitted to Public Hospitals in Southern Ethiopia, 2020: A Hospital-Based Case–Control Study

Abstract: Background A gush of amniotic fluid any time before the onset of labor is known as premature rupture of the membranes (PROM). Its consequences vary from maternal and neonatal mortality and morbidity to country-wide economic loss. At the national level in general, and in the study area in particular, little is known about PROM and its determinants. Hence, this study aimed at identifying determinants of PROM among pregnant women admitted to public hospitals in Southern Ethiopia, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
5
12
0
Order By: Relevance
“…Roopa S et al 17 from India also reported postpartum hemorrhage (32.8%) as leading cause of MNM followed by hypertensive disorder of pregnancy (23.6%) in their study. Post-partum hemorrhage is the most important cause of MNM in many other studies conducted by Galvao et al 18 in Brazil, Gupta et al 19 in India and Habte et al 20 in Africa. In contrast to our study, hypertension in pregnancy was the main cause of MNM in other studies conducted by Shrestha et al 21 in Nepal, Patankar et al 22 in India and Liyew et al 23 in Africa.…”
Section: Discussionmentioning
confidence: 91%
“…Roopa S et al 17 from India also reported postpartum hemorrhage (32.8%) as leading cause of MNM followed by hypertensive disorder of pregnancy (23.6%) in their study. Post-partum hemorrhage is the most important cause of MNM in many other studies conducted by Galvao et al 18 in Brazil, Gupta et al 19 in India and Habte et al 20 in Africa. In contrast to our study, hypertension in pregnancy was the main cause of MNM in other studies conducted by Shrestha et al 21 in Nepal, Patankar et al 22 in India and Liyew et al 23 in Africa.…”
Section: Discussionmentioning
confidence: 91%
“…The discrepancy findings between studies could be attributed to factors such as maternal comorbidities, socioeconomic status of women, and previous obstetric and delivery histories. Previous studies indicated that preterm PROM was attributed to these factors (17)(18)(19). Type of pregnancy (single vs. multiple), intrauterine infection, trauma, poor nutrition during pregnancy, vaginal bleeding, educational level, race, sociodemographic factors, genetic predisposition, and uterine over distention were also contributed to preterm PROM (20-23).…”
Section: Rate Of Preterm Prommentioning
confidence: 99%
“…(5) . Worldwide it is reported that the prevalence of PPROM shows a great variation between different countries whereby in Uganda (13.8%), Brazi (3.1%), Manipur, India (2.2%), (17) Bangladesh (8%), Egypt (5.3%), and Oman (1.8%). (30) As the time between the rupture of the membranes and the onset of labor increases, so may the risk of maternal and fetal infection.…”
Section: Introductionmentioning
confidence: 99%